2021
DOI: 10.1002/ccr3.4789
|View full text |Cite
|
Sign up to set email alerts
|

Urgent percutaneous transluminal septal myocardial ablation for left ventricular outflow tract obstruction exacerbated after surgical aortic valve replacement

Abstract: Percutaneous transluminal septal myocardial ablation (PTSMA) is an established procedure for treating symptomatic hypertrophic obstructive cardiomyopathy. We report a case of urgent PTSMA for treating refractory heart failure due to exacerbated obstruction of the left ventricular outflow tract after surgical aortic valvular replacement to treat severe aortic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Owing to its minimal invasiveness, septal ablation of the ventricular septum is more acceptable to patients ( 13 ). Prospective studies have shown that the mortality rate of patients within 30 days is 1%, and the survival rates after 1, 5, and 10 years are 98%, 89%, and 77%, respectively ( 14 ). However, this procedure is not suitable for patients with a septal thickness <15 mm, no suitable perforating artery of the ventricular septum, or prolonged occlusion of the collateral branches of the target perforating artery ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Owing to its minimal invasiveness, septal ablation of the ventricular septum is more acceptable to patients ( 13 ). Prospective studies have shown that the mortality rate of patients within 30 days is 1%, and the survival rates after 1, 5, and 10 years are 98%, 89%, and 77%, respectively ( 14 ). However, this procedure is not suitable for patients with a septal thickness <15 mm, no suitable perforating artery of the ventricular septum, or prolonged occlusion of the collateral branches of the target perforating artery ( 15 ).…”
Section: Discussionmentioning
confidence: 99%